Almaty-bishkek economic corridor tourism master plan. (Asian Development Bank, 2019)
In Central West Asia, the area between Almaty in Kazakhstan and Bishkek in the Kyrgyz Republic is home to exceptional heritage and a wealth of cultural and natural assets. The tourism potential is immense, but remains largely untapped. This plan identifies key tourism investment priorities such as developing ski resorts along the mountain range between Almaty and Issyk-Kul and linking these winter sport facilities with summer tourism opportunities. It also proposes transport infrastructure improvements, including enhancing Almaty International Airport as the major gateway to the region.